The Effect of a Combined Versus a Conventional Cognitive-Behavioral Therapy on Quality of Life for Comorbid Panic Disorder With Agoraphobia and Generalized Anxiety Disorder: Preliminary Results. (January 2014) - Primiano, Sandra; Marchand, André; Gosselin, Patrick; Langlois, Frédéric; Bouchard, Stéphane; Bélanger, Claude; Labrecque, Joane; Dugas, Michel; Dupuis, Gilles
Concurrent panic disorder with agoraphobia (PDA) and generalized anxiety disorder (GAD) are the most common diagnostic occurrences among anxiety disorders. This particular comorbidity is associated with significant impairments in quality of life (QOL). The current study sought to investigate the efficacy of a combined cognitive-behavioral psychotherapy that addressed both conditions compared with a conventional psychotherapy, which attends solely to the primary disorder. The hypotheses postulated firstly, that both treatment conditions would lead to improvements in participants' QOL and secondly, that the combined therapy would lead to greater QOL ameliorations. Twenty-five participants with comorbid PDA/GAD diagnoses were evaluated with a number of clinical interviews and self-report questionnaires, and were provided with either conventional or combined cognitive-behavioral psychotherapy, which consisted of 14 one-hour weekly sessions. Participants were once again evaluated in the same fashion 2-weeks after the completion of the psychotherapy. The results revealed that both conditions led to significant improvements in participants' QOL, but that the two groups did not significantly differ in terms of the effect on QOL. The results also reveal that the two conditions did not significantly differ in terms of their effect on PDA and GAD symptomatology or psychiatric comorbidity. The results demonstrate that the combined psychotherapy, which addresses both conditions simultaneously, is similar to the conventional psychotherapy employed for the primary disorder in terms of QOL enhancement, symptom severity, and comorbidity reduction.